Joint Hypermobility Links Neurodivergence to Dysautonomia and Pain - Csecs, Jenny L. L.; Iodice, Valeria; Rae, Charlotte L.; Brooke, Alice; Simmons, Rebecca; Quadt, Lisa; Savage, Georgia K.; Dowell, Nicholas G.; Prowse, Fenella; Themelis, Kristy; Mathias, Christopher J.; Critchley, Hugo D.; et al. (Frontiers in Psychiatry, 2022)
Objective: Autism, attention deficit hyperactivity disorder (ADHD), and tic disorder (Tourette syndrome; TS) are neurodevelopmental conditions that frequently co-occur and impact psychological, social, and emotional processes. Increased likelihood of chronic physical symptoms, including fatigue and pain, are also recognized. The expression of joint hypermobility, reflecting a constitutional variant in connective tissue, predicts susceptibility to psychological symptoms alongside recognized physical symptoms. Here, we tested for increased rates of joint hypermobility, autonomic dysfunction and musculoskeletal symptoms in 109 adults with neurodevelopmental condition diagnoses. Method: Prevalence of generalized joint hypermobility (GJH, hereon hypermobility) in adults with a formal diagnosis of neurodevelopmental conditions (from here on neurodivergent group, n=109) were compared to those in the general population in UK. Levels of orthostatic intolerance and musculoskeletal symptoms were compared to a separate comparison group (n=57). Age specific cut-offs for GJH were possible to determine in the neurodivergent and comparison group only. Results: The neurodivergent group manifested elevated prevalence of hypermobility (51%) compared to the general population (20%) and a comparison population (17.5%). Using a more stringent age specific cut-off, in the neurodivergent group this prevalence was 28.4%, more than double than the comparison group (12.5%) Odds ratio for presence of hypermobility in neurodivergent group, compared to the general population was 4.51 (95% CI 2.17 – 9.37), with greater odds in females than males. Using age specific cut-off, the odds ratio for GJH in neurodivergent group, compared to the comparison group, was 2.84 (95% CI 1.16 - 6.94). Neurodivergent participants reported significantly more symptoms of orthostatic intolerance and musculoskeletal skeletal pain than the comparison group. The number of hypermobile joints was found to mediate the relationship between neurodivergence and symptoms of both dysautonomia and pain. Conclusions: In neurodivergent adults, there is a strong link between the expression of joint hypermobility, dysautonomia and pain, more so than in the comparison group. Moreover, joint hypermobility mediates the link between neurodivergence and symptoms of dysautonomia and pain. Increased awareness and understanding of this association may enhance the management of core symptoms and allied difficulties in neurodivergent people, including co-occurring physical symptoms, and guide service delivery in the future.